Real-Time CT-Guided Spinal Biopsy with a Disposable Stereotactic Device: A Technical Note - Chakeres, Donald; Slone, Wayne; Christoforidis, Greg; Bourekas, Eric (American Journal of Neuroradiology, 2002)
Summary: We compared eight spinal needle biopsy procedures performed with an investigational disposable real-time stereotactic device and eight spinal needle freehand biopsies in which a standard technique was used, to determine whether the investigational device added value to the procedure. The device uses a simple stereotactic diaphragm pattern to define two vector points. The procedures in which the device was used were completed in 38% less time, using 50% fewer images, with considerably improved spatial accuracy and increased operator confidence, despite the device learning curve.